INDONESIAN ENGLISH ACCENT: PRIDE, PREJUDICE, AND INTELLIGIBILITY - Adam Adam; Sri Langgeng Ratnasari; Desi Surlitasari Dewi; Mega Aulia Ardhi; Nadia Putri Yudani (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2025)
This narrative examines the Indonesian English (IE) accent as a complex site of sociopolitical and linguistic negotiation within the broader context of the global expansion of English and the increasing diversification of its users, where the status of localized English varieties has become a central concern in contemporary sociolinguistics and applied linguistics. Framed by the grand theories of World Englishes and decolonial thought, this study explores Indonesian English beyond mere linguistic features. It examines the intersection of IE with identity, power, and historical legacies as well as responds to ongoing debates concerning linguistic legitimacy, ownership of English, and the persistence of colonial language ideologies in modern communication practices. Employing a narrative review methodology, this research synthesizes and analyzes scholarly literature published between 1990 and 2024, integrating foundational theoretical contributions with recent empirical developments to ensure both historical depth and contemporary relevance. The analysis is applied through the lenses of decolonial and World Englishes frameworks to examine the linguistic, sociolinguistic, educational, and technological aspects of Indonesian English. This approach enables a comprehensive understanding of how IE is constructed, evaluated, and contested across institutional and social domains. The study identifies distinctive IE phonological traits as legitimate linguistic innovations, not errors, and notes their emergence as a marker of cultural identity that reflects processes of nativization and creative adaptation rather than linguistic deficiency. Findings reveal systemic prejudice against Indonesian English in various domains, with a persistent preference for Inner Circle norms. This prejudice operates through educational policies, professional practices, and digital communication technologies that continue to privilege particular accents in global communication. Evidence challenges traditional concepts of intelligibility and supports shared responsibility in communication. It emphasizes the collaborative nature of meaning-making between speakers and listeners in international contexts, rather than placing the burden of understanding solely on Indonesian English speakers. Accent discrimination against IE is linked to colonial legacies and the neoliberal commodification of English, where particular accents function as symbolic capital within global markets and reinforce unequal power relations and linguistic insecurity among non–Inner Circle speakers. This review advocates for Indonesia-led educational reforms, inclusive technologies, and pluricentric standards. It positions Indonesian English as both a linguistic system and an act of postcolonial resistance. This perspective challenges global English pedagogical norms and contributes to broader efforts to democratize global communication and reimagine English as a shared, diverse, and ethically grounded resource.